Pengaruh Work-Life Balance, Fleksibilitas Kerja, Dan Beban Kerja Terhadap Turnover Intention Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi pada ISP Swasta di Bandar Lampung) - Hakim, Lukmanul; Tantina; M. Hasan Ma’ruf (ITB AAS Indonesia Surakarta, 2025)
This study examines the influence of work-life balance, work flexibility, and workload on turnover intention, with job satisfaction acting as a mediating variable, among Generation Z employees working at private Internet Service Providers in Bandar Lampung. The research aims to explore how these factors contribute to employees' intentions to leave their organizations, providing insights for ISP companies to improve retention strategies. Using a quantitative approach, data were collected through surveys distributed to 100 employees, representing various departments within 10 private ISPs. The analysis utilizes path analysis to assess direct and indirect relationships among the variables. The findings indicate that work-life balance does not significantly affect job satisfaction but has a negative and significant impact on turnover intention. Conversely, work flexibility positively influences job satisfaction and significantly reduces turnover intention. Workload was found to negatively impact job satisfaction, but it did not have a significant direct effect on turnover intention. Job satisfaction was not shown to mediate the effects of work-life balance, work flexibility, and workload on turnover intention. The study concludes that work flexibility plays a critical role in enhancing job satisfaction and reducing turnover intention among Generation Z employees. Recommendations for ISP companies include the implementation of flexible work policies, improved workload management, and fostering a supportive work culture to enhance employee satisfaction and retention. Keywords: Work-life Balance, Work Flexibility, Workload, Job Satisfaction, Turnover Intention.